Pengaruh jumlah subkultur dan media sub-optimal terhadap pertumbuhan dan kemampuan regenerasi kalus tebu (Saccharum officinarum L.) (Effect of repeated subculture and suboptimum media on the growth of sugarcane calli (Saccharum officinarum L.)) - Hayati MINARSIH; . Suharyo; Imron RIYADI; Diah RATNADEWI (E-Journal Menara Perkebunan, 2016)
Sugarcane (Saccharum officinarum L.) is an important crop for sugar production. One attempt to increase sugarcane productivity is through micropropagation and quality improvement of sugarcane seedlings in vitro. This research aimed to study the effect of repeated subcultures on callus capacity for regeneration and plant survival in acclimatization phase, as well as the influence of suboptimum media on the recovery capability of sugarcane callus to proliferate in vitro. Fourth subcultured sugarcane callus derived from young leaves were used as material in this research. Basic medium of Murashige and Skoog (MS) added with 3 mg/L 2,4-D, 10% coconut water, and 3% sucrose was used for callus initiation. For callus regeneration, the MS medium was supplemented with 2 mg/L BAP, 0.2 mg/L IAA, 10% coconut water, and 3% sucrose. Study on the effect of subculture numbers consisted of three stages, i.e. initiation, regeneration, and acclimatization, while the study on resting phase or the use of sub-optimal media included six treatment media and two pathways. Results showed that the fifth subcultures produced embryoid callus (91%), the highest non mucilaginous callus (97%), and the highest abnormality rate (6%). Results from the suboptimum media treatment, showed that B pathway (4 week resting phase) was better than the A pathway (8 week resting phase), based on fresh weight and callus abnormality percentage. A and B pathways indicated that the growth of callus can be recovered when it was grown back to the normal media and 1.5D-MS treatment of the resting phase showed the best growth and appearance.